2005
DOI: 10.1093/molbev/msj008
|View full text |Cite
|
Sign up to set email alerts
|

Cryptic Speciation and Recombination in the Fungus Paracoccidioides brasiliensis as Revealed by Gene Genealogies

Abstract: Paracoccidioides brasiliensis is the etiologic agent of paracoccidioidomycosis, a disease confined to Latin America and of marked importance in the endemic areas due to its frequency and severity. This species is considered to be clonal according to mycological criteria and has been shown to vary in virulence. To characterize natural genetic variation and reproductive mode in this fungus, we analyzed P. brasiliensis phylogenetically in search of cryptic species and possible recombination using concordance and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

23
373
3
25

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 309 publications
(424 citation statements)
references
References 54 publications
23
373
3
25
Order By: Relevance
“…Our results [Carrero et al submitted] indicated that a particular isolate (Pb01) was basal and distant to all other isolates. Moreover, the genetic variation in coding regions of P. brasiliensis indicates that there may be more than the three phylogenetic species already reported in the morphological species P. brasiliensis [57]. Strain Pb01 is of interest, because this particular isolate is so far, the best studied isolate from a molecular point of view, as deduced from a thorough analysis of its transcriptome, that yielded 6,022 assembled groups from mycelium and yeast phase expressed sequence tags, covering about 80% of the estimated P. brasiliensis Pb01 genome [58].…”
Section: Molecular Phylogenymentioning
confidence: 93%
See 2 more Smart Citations
“…Our results [Carrero et al submitted] indicated that a particular isolate (Pb01) was basal and distant to all other isolates. Moreover, the genetic variation in coding regions of P. brasiliensis indicates that there may be more than the three phylogenetic species already reported in the morphological species P. brasiliensis [57]. Strain Pb01 is of interest, because this particular isolate is so far, the best studied isolate from a molecular point of view, as deduced from a thorough analysis of its transcriptome, that yielded 6,022 assembled groups from mycelium and yeast phase expressed sequence tags, covering about 80% of the estimated P. brasiliensis Pb01 genome [58].…”
Section: Molecular Phylogenymentioning
confidence: 93%
“…Based on phylogenetic analysis of 65 P. brasiliensis isolates, Matute et al [57] recently proposed three distinct phylogenetic species within P. brasiliensis: S1 (a paraphyletic group formed by 38 isolates of Argentinean, Brazilian, Peruvian and Venezuelan origins, plus an isolate from an Antarctic penguin), PS2 (six isolates, five of them of Brazilian origin, and one Venezuelan) and PS3 (21 Colombian isolates).…”
Section: Molecular Phylogenymentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, the failure to detect sexual structure does not signify the absence of such structures. Using this approach, Matute et al [84,85] were able to detect three cryptic species in P. brasiliensis, from which two are phylogenetic species (PS2, composed of Brazilian and Venezuelan isolates, and PS3, restricted to Colombia) and one is a paraphyletic species (S1, which has a wider habitat range across the endemic areas). They also observed that while S1 and PS2 were considered recombining sexual species, PS3 was shown to be clonal.…”
Section: Emergence Of New Variants Of the Pathogenmentioning
confidence: 99%
“…This method also provides information about the reproductive mode of the different divergent species, even without the isolation of sexual structures. Cryptic species have been detected by gene genealogies in important pathogenic fungi, such as C. immitis (separated into 2 species: C. immitis and C. posadasii) (Koufopanou et al 2001), H. capsulatum (separated into at least 7 species) (Kasuga et al 2003) and P. brasiliensis, which is now separated into at least four previously unrecognized species: S1 (species 1 from Brazil, Argentina, Paraguay, Peru and Venezuela), PS2 (phylogenetic species 2 from Brazil and Venezuela), PS3 (phylogenetic species 3 with 21 isolates from Colombia) (Matute et al 2006) and Pb01-like (from the central region of Brazil) (Carrero et al 2008, Teixeira 2008.…”
Section: Species Concept and Use Of Prp8 Intein For Phylogenetic Studmentioning
confidence: 99%